2015
DOI: 10.1021/acs.bioconjchem.5b00393
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Ciprofloxacin with Poly(2-oxazoline)s and Polyethylene Glycol via End Groups

Abstract: The antibiotic ciprofloxacin (CIP) was covalently attached to the chain end of poly(2-methyloxazoline) (PMOx), poly(2-ethyloxazoline) (PEtOx), and polyethylene glycol (PEG), and the antimicrobial activity of these conjugates was tested for Staphylococcus aureus, Streptococcus mutans, Escherichia coli, Pseudomonas aeruginosa, and Kleisella pneumoniae. Chemical structures of the conjugates were proven by (1)H NMR and electron spray ionization mass spectrometry. The direct coupling of PMOx and CIP resulted in low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 49 publications
0
53
1
Order By: Relevance
“…Several independent studies show that poly(2‐ethyl‐2‐oxazoline) (PETOx) and poly(2‐methyl‐2‐oxazoline) (PMeOx) exhibit very low cytotoxicity and have no other side effects in immune systems . Moreover, even PETOx containing a certain amount of functional groups did not demonstrate any in vitro cytotoxic effects . Recent studies on a hemotoxicity of PMeOx and PETOx conjugates with enzymes and drugs confirmed even higher values of their hemolytic concentration with 50% red blood cells lysed (HC 50 ) compared to poly(ethylene glycol) (PEG) conjugates .…”
Section: Introductionmentioning
confidence: 99%
“…Several independent studies show that poly(2‐ethyl‐2‐oxazoline) (PETOx) and poly(2‐methyl‐2‐oxazoline) (PMeOx) exhibit very low cytotoxicity and have no other side effects in immune systems . Moreover, even PETOx containing a certain amount of functional groups did not demonstrate any in vitro cytotoxic effects . Recent studies on a hemotoxicity of PMeOx and PETOx conjugates with enzymes and drugs confirmed even higher values of their hemolytic concentration with 50% red blood cells lysed (HC 50 ) compared to poly(ethylene glycol) (PEG) conjugates .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Du et al (29) conjugated PEG (5,000 Da) to tobramycin and reported increased efficacy against in vivo Pseudomonas aeruginosa biofilm. Another study showed that ciprofloxacin could be conjugated to PEG (2,000 Da), and this enhanced antibiotic efficacy against both Gram-negative and -positive bacteria (30). Our experiments did not involve conjugation between the osmotic agents and antibiotics, although this is probably requisite for successful applications in vivo.…”
Section: Fig 4 Legend (Continued)mentioning
confidence: 88%
“…The hemocompatibility of the prepared polymers was explored and HC 50 (hemolytic concentration at with 50% blood cells is lysed) was determined with use of porcine blood cells. All values were above 5000 µg/cm 3 indicating low hemotoxicity of the conjugates obtained [42].
…”
Section: Polymersmentioning
confidence: 99%
“…Poly(2-oxazoline)s (POx) are also non-toxic polymers with adjustable hydrophilicity and easily modified end-groups [ 41 ]. The antibiotic ciprofloxacin was covalently attached to the chain of poly(2-methyloxazoline) (PMOx), poly(2-ethyloxazoline) (PEtOx), and PEG (Scheme 4 ) [ 42 ]. Anti-microbial activity of the novel conjugates was tested against S. aureus , Streptococcus mutans , E. coli , P. aeruginosa, and K. pneumoniae .…”
Section: Polymersmentioning
confidence: 99%